1992
DOI: 10.1007/bf02598096
|View full text |Cite
|
Sign up to set email alerts
|

Clinical activities and satisfaction of general internists, cardiologists, and ophthalmologists

Abstract: To define factors that affect the levels of practice satisfaction of different specialities, an observer recorded the activities of 15 physicians in practice (nine general internists, three cardiologists, and three ophthalmologists) as they examined 304 clinic patients. General internists reported less satisfaction with their clinics than did the other physicians and attributed their satisfaction primarily to successful social interaction in 54% of visits, while cardiologists most often derived satisfaction fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
2
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
3
2
1
Order By: Relevance
“…However, higher job satisfaction rates were found in studies conducted in developed countries like Canada and USA physicians in which overall job satisfaction was reported by 75.5%, 74% and 81% of the doctors respectively. [24][25][26] While the mean score of job satisfaction scale were quite high in British, Australian and Lithuanian medical practitioners showing a wide variation from the present study.…”
Section: Discussioncontrasting
confidence: 58%
“…However, higher job satisfaction rates were found in studies conducted in developed countries like Canada and USA physicians in which overall job satisfaction was reported by 75.5%, 74% and 81% of the doctors respectively. [24][25][26] While the mean score of job satisfaction scale were quite high in British, Australian and Lithuanian medical practitioners showing a wide variation from the present study.…”
Section: Discussioncontrasting
confidence: 58%
“…This finding is consistent with several studies conducted in developed counties. A study of Canadian physicians reported an overall job satisfaction of 75.5% (21), and in the USA obstetrician – overall job satisfaction of gynecologists and ophthalmologist was reported to be 74% (22) and 81% (23), respectively. British medical practitioners gave a mean score of 19.5 on a job satisfaction scale of 5–25 (24), an Australian study reported a mean score of 5.66 out of seven (25), and a Lithuanian paper reported an overall job satisfaction mean score of 4.06 out of five (26).…”
Section: Discussionmentioning
confidence: 99%
“…17 A much larger study, however, showed that levels of dissatisfaction were actually lowest in such primary care subspecialties as geriatrics and infectious diseases and were highest in such surgical subspecialties as gynecology, otolaryngology, and plastic surgery. In one small study, researchers compared the professional satisfaction that general internists, cardiologists, and ophthalmologists said they derived from outpatient work.…”
Section: Medical Specialtymentioning
confidence: 98%